Report of Two Cases of Pediatric IgG4-Related Lymphadenopathy (IgG4-LAD): IgG4-Related Disease (IgG4-RD) or a Distinct Clinical Pathological Entity? - Mariaclaudia Meli; Marta Arrabito; Lucia Salvatorelli; Rachele Soma; Santiago Presti; Maria Licciardello; Vito Miraglia; Maria Grazia Scuderi; Giuseppe Belfiore; Gaetano Magro; Giovanna Russo; Andrea Di Cataldo (MDPI AG, 2022)
IgG4-related disease (IgG4-RD) is a recently discovered immune-mediated fibroinflammatory condition, uncommon in the pediatric population, that could involve multiple organs and induce cancer-like lesions and organ damage. Its main features are multiple injuries in different sites, a dense lymphoplasmacytic infiltrate rich in IgG4 plasma cells, storiform fibrosis, and often high serological concentrations of IgG4. Autoimmune pancreatitis is the most common manifestation, mainly in adults. Two cases of IgG4-RD in children with lymph node localization of disease are reported. Localized or systemic lymph node involvement is common, but lymph node enlargement as the first and only manifestation of IgG4-RD is unusual, and therefore, hard to differentiate from other diseases. IgG4-related lymphadenopathy (IgG4-LAD) is most likely a distinct disease, described as isolated lymphadenopathy, related to the presence of elevated numbers of IgG4-positive plasma cells. Both disorders are likely to be misdiagnosed in children because they are characterized by rare and polymorphic features. IgG4-RD and IgG4-LAD should be considered in the differential diagnosis of disorders characterized by lymphadenopathy of uncertain etiology.